Data Envelopment Analysis and Tobit Analysis for Firm Efficiency in Perspective of Working Capital Management in Manufacturing Sector of Pakistan - Ahmad, Muhammad Fawad; Ishtiaq, Muhammad; Hamid, Kashif; Khurram, Muhammad Usman; Nawaz, Ali (International Journal of Economics and Financial Issues, 2017)
This research is performed for dealing with some of the important working capital management policies and efficiency regarding to manufacturing sector of Pakistan. For this purpose data from 37 firms have been taken for the period 2009-2014. Data envelopment analysis (DEA) and Tobit regression analysis has been performed to achieve the objective of this study. DEA results indicate that only fifteen companies require increase in inputs to attain better output whereas six companies require decrease in the input. However sixteen companies have to consistent with their existing proportionate of inputs to sustain the output maximization. Tobit regression analysis concludes that average collection period has significant negative impact on efficiency and current ratio, gross working capital turnover ratio and financial leverage ratio have positive significant impact on efficiency. Keywords: Working Capital Management, Efficiency, Data Envelope Analysis, Tobit Analysis, Manufacturing Sector JEL Classifications: C8, G3